2010
DOI: 10.1149/1.3464803
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and Electronic Conductivities and Fuel Cell Performance of Oxygen Excess-Type Lanthanum Silicates

Abstract: Highly dense pellets of an oxygen excess-type lanthanum silicate ͑La 9.333+x Si 6 O 26+1.5x , x Ͼ ca. 0.3, OE-LSO͒ were successfully fabricated, and their electrical conducting properties were studied. The replacement of Si by Al enhanced its conductivity, and the slightly Al-doped OE-LSO specimen ͓La 9.62 ͑Si 5.79 Al 0.21 ͒O 26.33 ͔ had excellent features as a solid electrolyte; that is, it had high ionic conductivity and was highly stable under reducing as well as oxidizing conditions at 873-1073 K. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…Thus, one of the major challenges in the development of intermediate temperature SOFCs is to develop a solid oxide electrolyte material with a high conductivity to maintain the low electrolyte resistance during operation. Lanthanum silicate oxyapatite is emerging as new class of oxide ion conductors and a substantial level of oxygen ionic transport has been reported for apatite type phases A 10−y Si 6 O 26±ı , where A corresponds to rare-earth and alkaline-earth metal cations [1][2][3][4][5][6][7][8][9][10][11][12][13]. The apatite lattice consists of covalent SiO 4 tetrahedra and ionic-like La/O channels [4,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one of the major challenges in the development of intermediate temperature SOFCs is to develop a solid oxide electrolyte material with a high conductivity to maintain the low electrolyte resistance during operation. Lanthanum silicate oxyapatite is emerging as new class of oxide ion conductors and a substantial level of oxygen ionic transport has been reported for apatite type phases A 10−y Si 6 O 26±ı , where A corresponds to rare-earth and alkaline-earth metal cations [1][2][3][4][5][6][7][8][9][10][11][12][13]. The apatite lattice consists of covalent SiO 4 tetrahedra and ionic-like La/O channels [4,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were obtained from a mixture of raw powders of La 2 O 3 (99.99% purity, Kishida Chemical Co., Ltd.), SiO 2 (99% purity, Kishida Chemical Co., Ltd.), and Al(OH) 3 (99.5% purity, Kishida Chemical Co., Ltd.). Finally, powders were pressed into a disk at 57 MPa, followed by sintering at 1973 K for 10 h in air as described elsewhere [10]. After the thickness of the obtained disk (17 mm in diameter) was adjusted to 1.0 mm, LSCF and platinum pastes were applied on each surface of the disk (electrode surface area: 0.38 cm 2 ), and used as working and counter electrodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the oxygen excess-type Al-doped LSO, La 10 (Si 5.8 Al 0.2 )O 26.9 on weighted basis (OE-ALSO) was the best composition as a solid electrolyte [9] because of its high electrical conductivity (6.3 Â 10 À2 S cm À1 at 1073 K [10]), high ionic transport number (>0.996 at 1073 K [10,11]), high chemical stability under presence of carbon dioxide as well as under the reducing conditions [12], and high ability to construct efficient electrode/electrolyte interfaces using MIEC electrode [10]. In addition, we have examined its potential as the solid oxide fuel cell (SOFC) electrolyte, and reported that a maximum power density of ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineshige et al measured the average transference number of oxygen ions in La 9.67 (SiO 4 ) 6 O 2.535 ceramics using an oxygen concentration cell over the p O2 range of 10 ¹2 10 ¹24 at 873 and 1073 K. 148) They concluded that the average transference number of oxygen ions was greater than 0.99 under the aforementioned conditions. However, measurement of the transference number at temperatures above 1173 K would be necessary to allow a comparison with the results reported in their previous study, 125) because hole conductivity may have influenced the results.…”
Section: )mentioning
confidence: 99%